Inheritance of resistance to pepper veinal mottle virus in chilli - Soh, A. C.; Yap, T. C.; Graham, K. M. (American Phytopathological Society, 1977)
Classical Mendelian analyses of the results of a greenhouse test using an isolate of pepper veinal mottle virus (PVMV) and of a field test with natural infection gave strong indication of a recessive gene conditioning resistance to veinal mottle virus in chilli. Additive effectsalso played some role in the expression of PVMV resistance and its heritability estimate was high. Results of systemic virus assays suggested that the resistance gene functioned by partially inhibiting virus multiplication.